2017
DOI: 10.1111/1467-9604.12181
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Encountered by 17 Autistic Young Adults in Hong Kong

Abstract: The self‐portrayals of 17 young persons with autism spectrum disorder reveal the challenges encountered by them, including study problems, inter‐personal relationships, being bullied by classmates at school, discrimination by the public in general and teachers, social workers, and peers in particular, obstacles to post‐secondary education, difficulties in securing and maintaining employment, psychological distress, and so on. This may indicate ineffective inclusive education and practice even though the govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…They found that partial or complete absenteeism assessed at school was present in 42.6% of students with ASC, compared with 7.1% of TD students during a 20-day period (Munkhagen et al 2017). A number of studies have problematized the finding that students with ASC are at greater risk of being bullied than their TD peers (Fernando and Perera 2012;Hwang et al 2018;Wong 2017;Sreckovic et al 2014). This phenomenon might also be linked to the difficulties sometimes faced by students with ASC in expressing their emotions regarding situations related to the school setting (Able et al 2015;Twachtman-Cullen et al 2006).…”
Section: Individuals With Asc Without Id During Adolescencementioning
confidence: 99%
“…They found that partial or complete absenteeism assessed at school was present in 42.6% of students with ASC, compared with 7.1% of TD students during a 20-day period (Munkhagen et al 2017). A number of studies have problematized the finding that students with ASC are at greater risk of being bullied than their TD peers (Fernando and Perera 2012;Hwang et al 2018;Wong 2017;Sreckovic et al 2014). This phenomenon might also be linked to the difficulties sometimes faced by students with ASC in expressing their emotions regarding situations related to the school setting (Able et al 2015;Twachtman-Cullen et al 2006).…”
Section: Individuals With Asc Without Id During Adolescencementioning
confidence: 99%
“…Paralelamente, otros estudios muestran la falta de recursos para ayudar al alumnado emigrante que, en ocasiones, se ve marginado y no se fomenta su participación por parte de toda la comunidad docente o del entorno social para integrarlos. Además, existe una investigación de Wong (2017) que recoge una experiencia en un colegio. Observa cómo 17 jóvenes con autismo estando en una escuela inclusiva perciben problemas al estar con los demás ocurriendo bullying y se determina cómo la inclusión por sí sola no es efectiva.…”
Section: Resultsunclassified
“…Research findings indicate that students with SEN face a larger risk of being victimised regarding their academic and social achievements, being teased, rejected, and bullied (Katz et al., 2012; Mamas et al., 2019, Wong, 2017). These findings are corroborated by the current study, whose participants revealed socio‐emotional distress from perceived rejection from peers.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Asian countries research focusing the participation of students with SEN has not garnered much attention. Where research exists, students report that they face a range of challenges when included in general classes, including difficulties in handling academic subjects and not being listened to by teachers (Lam and Yeung, 2005), displaying signs of stress caused by the amount and level of homework (Cheng and Chang, 2014), and experiencing rejection and bullying (Wong, 2017). Conversely, emotional support from teachers was found to have positive effects on students (Chmiliar, 2009; Mamas et al., 2019).…”
Section: Introductionmentioning
confidence: 99%